(untitled) (Bangladesh Journal of Botany, 2025)
Soil physicochemical and biological properties are key determinants of ecosystem functioning in tropical deciduous forests. This study investigated the spatial and vertical variability of soil characteristics and microbial activity in the Bhawal (BNP) and Madhupur (MNP) Sal forests of Bangladesh. Rhizosphere soil samples were collected from two depths to analyze physicochemical and biological parameters. Two-way ANOVA, correlation, regression, and NMDS analyses were applied to evaluate variation and interrelationships. Significant spatial and vertical differences (p <0.001) were observed, where Madhupur exhibiting higher OC, TN, CEC, and microbial activity than Bhawal. Upper soil layers showed greater microbial abundance and respiration, while deeper layers had higher sodium but lower biological activity. Regression analysis identified OC, TP, and Na as key positive predictors of soil respiration, whereas CEC had a negative influence. NMDS ordination distinguished samples by site and depth, emphasizing the dominant role of nutrient and microbial factors in soil variability. Overall, soil heterogeneity in the Sal forests is primarily governed by organic matter and microbial processes, with anthropogenic disturbance reducing fertility in Bhawal. Bangladesh J. Bot. 54(4): 967-975, 2025 (December)